Bioequivalence of a new liquid formulation of benazepril compared with the reference tablet product. Issue 8 (26th July 2013) - Kelers, K; Devi, JL; Anderson, GA; Zahra, P; Vine, JH; Whittem, T
<x xml:space="preserve">Abstract</x> Objective To compare the bioequivalence and 'switchability' of two formulations of benazepril (tablet and liquid) after oral administration. Design Randomised cross‐over design, followed by parallel comparison. Methods Twelve mixed‐breed dogs were administered either a tablet (Group A) or liquid formulation (Group B) of benazepril orally at 0.45 mg/kg daily for 4 days. With no washout period, the dogs then received the alternative treatment at the same dose for a further 4 days. Blood samples taken prior to treatment and serially after treatment were analysed for plasma concentrations of benazepril and benazeprilat and the activity and concentration of angiotensin‐converting enzyme (ACE). The calculated percentage inhibition of ACE was defined as the primary outcome variable. Results No statistically significant differences were found between groups A and B for any variable evaluated. The mean (± SD) percentage of ACE inhibition was 85.5 ± 7.04% for the liquid formulation and 85.9 ± 6.66% for the tablet formulation. The mean of the ratios was 1.00 (80% confidence interval 0.96–1.04). No evaluated effect term (sequence, formulation or period) had any statistical effect on any outcome variable. Conclusion This study supports a conclusion that, based on pharmacodynamic response, the liquid formulation of benazepril is bioequivalent to the reference tablet formulation. Further, the lack of a sequence effect supports the switchability of these two formulations.